(untitled) - Kotov, Nicholas A. (New York, 2006)
This volume is a delightful read for chemists, as it highlights the important role organic, bioorganic, and inorganic chemists must play in advancing nanotechnology. It is targeted for a chemical audience with an advanced degree in chemistry and a good background in all the traditional disciplines. …The book certainly highlights the important role chemists must play in future developments of nanotechnology, particularly in regard to nanoparticle assembly and superstructure synthesis.
Keywords: Nanoscience,Nanostructured materials,Nanotechnology,Nanoparticles; Electric properties